Status, determinants and risk factors of all-cause dementia in South Asia: Findings from a preliminary analysis of global health data - Palliyaguru, D.L.; Palliyaguru, N.; Teixeira, C.V.L.; Armstrong, N.M.; Liyanage, S.; Senarath, U.; Arambepola, C.; Jayasinghe, Saroj; Dalpatadu, C. (MedRxiv, 2024)
South Asia is one of the most populous regions of the world. At present, South Asians make up more than 25% of the world’s population but little effort has been dedicated to studying trends and etiological factors driving aging and aging-related conditions in this part of the world. Even less characterization has been done on brain-related conditions, particularly all-cause dementia in South Asia. To address this, we examined data from the US Census Bureau, World Health Organization Global Dementia Observatory and the Global Burden of Disease (GBD) 2019 Study, and conducted a comparative analysis of population statistics, dementia as a priority health area, and dementia incidence rates, death rates and disability-adjusted life years (DALYs) in 8 South Asian countries – Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. Our analysis reiterated that there are limited resources dedicated to dementia in this region. Sri Lanka and Afghanistan had the highest dementia crude rates and age-standardized rates, respectively. The burden of dementia in some South Asian countries was comparable to estimated global averages, and was largely driven by population aging. Analyses of available data on known biological, behavioral, environmental and disease risk factors, highlighted the role of metabolic risk factors such as high fasting blood glucose. Here, we also underscore the critical need for future follow-up longitudinal studies focusing on brain aging and dementia and describe a roadmap for designing them - taking into account cultural, economic and public health dynamics that may be uniquely applicable to countries in South Asia.
Keywords: dementia; South Asia; Global Health; Public Health